An Ultrathin Asymmetric Solid Polymer Electrolyte with Intensified Ion Transport Regulated by Biomimetic Channels Enabling Wide‐Temperature High‐Voltage Lithium‐Metal Battery. Issue 12 (5th February 2023) - Yao, Meng; Ruan, Qinqin; Pan, Shanshan; Zhang, Haitao; Zhang, Suojiang
Abstract: Solid electrolytes that can be made compatible with high‐voltage cathodes are greatly desired to increase the energy density of solid lithium metal batteries (SLMBs). However, no monophase polymer or ceramic examples can simultaneously exhibit strong electrochemical stability and reasonable lithium compatibility due to their limited internal energy gap. Herein, a novel asymmetric solid polymer electrolyte (AMSE) with tailored Li + transport mechanisms is proposed. It is composed of a high‐voltage layer (HVL, polyacrylonitrile/ionic liquid [IL]) and lithium‐compatible layer (LCL, poly(vinylidene fluoride‐ co ‐hexafluoropropylene)/UiO‐66‐SO3 Li). The HVL exhibits a vehicular Li + transport mechanism with the introduction of IL, which achieves exceptional‐electrochemical stability and reduced interfacial resistance. Due to the complexation between anions and UiO‐66‐SO3 Li, a structural diffusion mechanism is achieved in LCL, realizing a quasi‐single‐ion migration in biomimetic ionic channels. The as‐proposed asymmetric configuration, combined with the transport mechanisms, leads to a gradient distribution of electric potential and Li + in the electrolyte, thus realizing a stable Li + flux, which is proved by COMSOL‐Multiphysics. The AMSE‐based SLMBs and scale‐up pouch cells show remarkable cycling stability at 4.3 V from room temperature (Li/LiNi0.8 Mn0.1 Co0.1 O2, 3.27 mAh cm −2 ) to 100 °C. The strategy of facilitating the transport mechanism is expected to provide new pathways for designing next‐generation SLMBs with high energy density. Abstract : This work highlights the great application potential of solid polymer electrolytes with asymmetric configuration and modulated ion transport ability. The reported high‐voltage layer exhibits vehicular Li + transport mechanism with exceptional‐electrochemical stability and reduced interfacial resistance, while the lithium compatible layer realizes quasi‐single‐ion migration. The as‐proposed asymmetric configuration, combined with the transport mechanisms, leads to excellent electrochemical properties for the resulting high‐voltage lithium metal batteries.